The Litter Queen Supplementary Reading Material - Roderick Hunt; Roderick Hunt (Oxford Reading Tree, 2012)
The Litter Queen | Oxford Reading Tree Stories | ORT Stage 9 | Kids Books | English Audiobooks Wilma's mum and dad took children to a picnic on a hill. After picnic Wilma's mum ask children to collect all the litter and Floppy got injured because of the litter.